Social Masks and Identity Construction in Lualhati Bautista’s Bata... Pa'no Ka Ginawa? - Marie Rose L. Costes (RIRAI Publisher, 2024)
This research employs a descriptive qualitative method, combining textual analysis with cultural and socio-cultural perspectives, to investigate the portrayal of social masks, identity construction, and resilience in Lualhati Bautista's novels, focusing on